2011
DOI: 10.1371/journal.pone.0022671
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular DExD/H-Box RNA-Helicases UAP56 and URH49 Exhibit a CRM1-Independent Nucleocytoplasmic Shuttling Activity

Abstract: Cellular DExD/H-box RNA-helicases perform essential functions during mRNA biogenesis. The closely related human proteins UAP56 and URH49 are members of this protein family and play an essential role for cellular mRNA export by recruiting the adaptor protein REF to spliced and unspliced mRNAs. In order to gain insight into their mode of action, we aimed to characterize these RNA-helicases in more detail. Here, we demonstrate that UAP56 and URH49 exhibit an intrinsic CRM1-independent nucleocytoplasmic shuttling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 72 publications
3
9
1
Order By: Relevance
“…As in mammalian cells, D. melanogaster and C. elegans [8], [11], [47], both experiments demonstrated that Arabidopsis UAP56 is a predominantly nuclear protein. Recently, it was found that human UAP56 can shuttle between nucleus and cytosol [51], but from our results there is no clear indication for cytosolic localisation of UAP56 in Arabidopsis cells. Rice UAP56 fused to YFP was detected in both nucleus and cytosol of transiently transformed Arabidopsis protoplasts [29], which could be due to overexpression of the fusion protein or due to the use of a heterologous expression system.…”
Section: Discussioncontrasting
confidence: 90%
“…As in mammalian cells, D. melanogaster and C. elegans [8], [11], [47], both experiments demonstrated that Arabidopsis UAP56 is a predominantly nuclear protein. Recently, it was found that human UAP56 can shuttle between nucleus and cytosol [51], but from our results there is no clear indication for cytosolic localisation of UAP56 in Arabidopsis cells. Rice UAP56 fused to YFP was detected in both nucleus and cytosol of transiently transformed Arabidopsis protoplasts [29], which could be due to overexpression of the fusion protein or due to the use of a heterologous expression system.…”
Section: Discussioncontrasting
confidence: 90%
“…Our data also indicates that there is an additional TAP/p15-dependent step that also occurs within speckles, and likely includes the recruitment of TAP to the mRNA. This step may be coupled with the release of UAP56/URH49, 37 , 38 although it is possible that UAP56/URH49 may stay on the mRNA and accompany it to the cytoplasm 39 . It is thus likely that egress of export-competent mRNAs from the speckles requires TAP/p15 recruitment, and this is consistent with recent findings 26 .…”
Section: Discussionsupporting
confidence: 85%
“…Importantly, although LGP2 is cytoplasmic and DDX39B nuclear, we found that endogenous DDX39B was also present in the cytoplasm (Fig. 3h), a finding previously noted [32][33][34]. Finally, to validate the role of LGP2 in promoting NF-κB activation in the setting of DDX39B loss, we re-expressed LGP2 in Lgp2 −/− MEFs.…”
Section: Ddx39b Inhibits Nf-κb In Association With Lgp2supporting
confidence: 72%